Download presentation

1
**Copyright © Zeph Grunschlag, 2001-2002.**

Proofs Zeph Grunschlag Copyright © Zeph Grunschlag,

2
**Agenda Proofs: General Techniques Direct Proof Indirect Proof**

Proof by Contradiction L14

3
**If k is any integer such that k 1 (mod 3),**

Proof Nuts and Bolts A proof is a logically structured argument which demonstrates that a certain proposition is true. When the proof is complete, the resulting proposition becomes a theorem, or if it is rather simple, a lemma. For example, consider the proposition: If k is any integer such that k 1 (mod 3), then k 3 1 (mod 9). Let’s prove this fact: L14

4
Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) L14

5
Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3) L14

6
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n L14

7
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n n k = 3n + 1 L14

8
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n n k = 3n + 1 n k 3 = (3n + 1)3 L14

9
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n n k = 3n + 1 n k 3 = (3n + 1)3 n k 3 = 27n n 2 + 9n + 1 L14

10
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n n k = 3n + 1 n k 3 = (3n + 1)3 n k 3 = 27n n 2 + 9n + 1 n k 3-1 = 27n n 2 + 9n L14

11
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n n k = 3n + 1 n k 3 = (3n + 1)3 n k 3 = 27n n 2 + 9n + 1 n k 3-1 = 27n n 2 + 9n n k 3-1 = (3n 3 + 3n 2 + n)·9 L14

12
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n n k = 3n + 1 n k 3 = (3n + 1)3 n k 3 = 27n n 2 + 9n + 1 n k 3-1 = 27n n 2 + 9n n k 3-1 = (3n 3 + 3n 2 + n)·9 m k 3-1 = m·9 L14

13
**Proofs Example PROVE: kZ k 1(mod 3) k 31(mod 9) k 1(mod 3)**

n k-1 = 3n n k = 3n + 1 n k 3 = (3n + 1)3 n k 3 = 27n n 2 + 9n + 1 n k 3-1 = 27n n 2 + 9n n k 3-1 = (3n 3 + 3n 2 + n)·9 m k 3-1 = m·9 k 31(mod 9) L14

14
Direct Proofs Previous was an example of a direct proof. I.e., to prove that a proposition of the form “k P(k) Q(k)” is true, needed to derive that “Q(k) is true” for any k which satisfied “P(k) is true”. Three basic steps in a direct proof: L14

15
**Direct Proofs Deconstruct Axioms**

Take the hypothesis and turn it into a usable form. Usually this amounts to just applying the definition. EG: k 1(mod 3) really means 3|(k-1) which actually means n k-1 = 3n L14

16
**Direct Proofs Mathematical Insights**

Use your human intellect and get at “real reason” behind theorem. EG: looking at what we’re trying to prove, we see that we’d really like to understand k 3. So let’s take the cube of k ! From here, we’ll have to use some algebra to get the formula into a form usable by the final step: L14

17
**Direct Proofs Reconstruct Conclusion**

This is the reverse of step 1. At the end of step 2 we should have a simple form that could be derived by applying the definition of the conclusion. EG. k 31(mod 9) is readily gotten from m k 3-1 = m·9 since the latter is the definition of the former. L14

18
Proofs Indirect In addition to direct proofs, there are two other standard methods for proving k P(k) Q(k) Indirect Proof For any k assume: Q(k) and derive: P(k) Uses the contrapositive logical equivalence: P Q Q P L14

19
**Proofs Reductio Ad Absurdum**

Proof by Contradiction (Reductio Ad Absurdum) For any k assume: P(k) Q(k) and derive: P(k) Q(k) Uses the logical equivalence: P Q P Q P Q P Q (P Q ) (P Q ) (P Q ) (P Q ) (P Q ) (P Q ) Intuitively: Assume claim is false (so P must be true and Q false). Show that assumption was absurd (so P false or Q true) so claim true! L14

20
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) L14

21
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. L14

22
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. L14

23
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 L14

24
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n L14

25
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n n (k - 1)(k + 1) = 2n L14

26
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n n (k - 1)(k + 1) = 2n 2 | (k - 1)(k + 1) L14

27
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n n (k - 1)(k + 1) = 2n 2 | (k - 1)(k + 1) 2 | (k - 1) 2 | (k + 1) since 2 is prime L14

28
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n n (k - 1)(k + 1) = 2n 2 | (k - 1)(k + 1) 2 | (k - 1) 2 | (k + 1) since 2 is prime a k - 1 = 2a b k+1 = 2b L14

29
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n n (k - 1)(k + 1) = 2n 2 | (k - 1)(k + 1) 2 | (k - 1) 2 | (k + 1) since 2 is prime a k - 1 = 2a b k+1 = 2b a k = 2a + 1 b k = 2b – 1 L14

30
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n n (k - 1)(k + 1) = 2n 2 | (k - 1)(k + 1) 2 | (k - 1) 2 | (k + 1) since 2 is prime a k - 1 = 2a b k+1 = 2b a k = 2a + 1 b k = 2b – 1 In both cases k is odd L14

31
**Indirect Proof Example**

PROVE: The square of an even number is even. (Ex b) Suppose k 2 is not even. So k 2 is odd. n k 2 = 2n + 1 n k = 2n n (k - 1)(k + 1) = 2n 2 | (k - 1)(k + 1) 2 | (k - 1) 2 | (k + 1) since 2 is prime a k - 1 = 2a b k+1 = 2b a k = 2a + 1 b k = 2b – 1 In both cases k is odd So k is not even L14

32
**Rational Numbers an Easier Characterization**

Recall the set of rational numbers Q = the set of numbers with decimal expansion which is periodic past some point (I.e. repeatinginginginginging…) Easier characterization Q = { p/q | p,q are integers with q 0 } Prove that the sum of any irrational number with a rational number is irrational: L14

33
**Reductio Ad Absurdum Example –English!**

You don’t have to use a sequence of formulas. Usually an English proof is preferable! EG: Suppose that claim is false. So [x is rational and y irrational] [=P] and [x+y is rational] [= Q]. But y = (x+y ) - x. The difference of rational number is rational since a/b – c/d = (ad-bc)/bd. Therefore [y must be rational] [implies P ]. This contradicts the hypotheses so the assumption that the claim was false was incorrect and the claim must be true. You don’t need the bracketed symbols: [=P] [= Q] [ P P Q ] In the actual proof. These are added to point out where the symbolic version of Reductio Ad Absurdum is really being used. L14

34
Proofs Disrefutation Disproving claims is often much easier than proving them. Claims are usually of the form k P(k). Thus to disprove, enough to find one k –called a counterexample– which makes P(k) false. L14

35
**Disrefutation by Counterexample**

Disprove: The product of irrational numbers is irrational. L14

36
**Blackboard Exercise for 3.1**

Proof that the square root of 2 is irrational L14

Similar presentations

© 2019 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google